The adverse childhood experiences questionnaire: Two decades of research on childhood trauma as a primary cause of adult mental illness, addiction, and medical diseases - Emily M. Zarse; Mallory R. Neff; Rachel Yoder; Leslie Hulvershorn; Joanna E. Chambers; R. Andrew Chambers (Cogent Medicine, 2019)
Objective. In 1998, Felitti and colleagues published the first study of the Adverse Childhood Experiences-Questionnaire (ACE-Q), a 10-item scale used to correlate childhood maltreatment and adverse rearing contexts with adult health outcomes. This paper qualitatively reviews nearly two decades of research utilizing the ACE-Q, highlighting its contribution to our understanding of the causal roots of common, interlinked comorbidities of the brain and body. Methods. An OVID/PubMed search was conducted for English language articles published before 2016, containing the phrase “Adverse Childhood Experiences” in which the ACE-Q was utilized. Source review included a manual search of bibliographies, resulting in 134 articles, including 44 based on the original ACE-Q study population. Results. ACE-Q research has demonstrated that exposures to adverse childhood experiences converge dose-dependently to potently increase the risk for a wide array of causally interlinked mental illnesses, addictions, and multi-organ medical diseases. The intergenerational transmission of this disease burden via disrupted parenting and insecure rearing contexts is apparent throughout this literature. However, the ACE-Q does not tease out genetic or fetal drug exposure components of this transmission. Conclusions. Adverse childhood experiences and rearing may generate a public health burden that could rival or exceed all other root causes. Translating this information to health-care reform will require strengthening brain-behavioral health as core public and preventative health-care missions. Greater integration of mental health and addiction services for parents should be accompanied by more research into brain mechanisms impacted by different forms and interactions between adverse childhood experiences.